Conductive composition and method for producing same, conductor and method for producing same
The conductive composition, characterized by specific molecular weight ratios and containing an acidic group-containing conductive polymer and a basic compound, addresses the issue of foreign matter generation in film formation, achieving improved film uniformity and conductivity.
Patent Information
- Application Number
- JP2020555673
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-11-15
- Filing Date
- 2019-11-11
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2039-11-11
AI Technical Summary
Conductive compositions containing acidic group-containing conductive polymers face issues with the generation of foreign matter during film formation, leading to defects such as breaking of lines when exposed to electron beams.
A conductive composition with an area ratio (X/Y) of 0.046 or less, calculated using a specific evaluation method, and a ZS/ZR ratio of 20 or less, which involves the use of an acidic group-containing conductive polymer and a basic compound, along with a surfactant and a solvent, to minimize low molecular weight components and fluorescent substances.
The proposed conductive composition effectively reduces the generation of foreign matter in the coating film, enhancing the uniformity and conductivity of the film, while suppressing the transfer of acidic substances to the resist layer.
Smart Images

Figure 0007670487000010 
Figure 0007670487000011 
Figure 0007670487000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive composition and a method for producing the same, and a conductor and a method for producing the same. This application claims priority based on Japanese Patent Application No. 2018-214904, filed on November 15, 2018, the contents of which are incorporated herein by reference. [Background technology]
[0002] Pattern formation technology using charged particle beams such as electron beams and ion beams is expected to be the next generation technology of optical lithography. When using charged particle beams, it is important to improve the sensitivity of the resist layer in order to improve productivity. Therefore, the mainstream technology is to use highly sensitive chemically amplified resists, which generate acid in the exposed areas or areas irradiated with a charged particle beam, followed by a heating process called post-exposure bake (PEB) to promote crosslinking or decomposition reactions. Furthermore, in recent years, with the trend toward miniaturization of semiconductor devices, there has been a demand for control of resist shapes on the order of several nm.
[0003] However, in a pattern formation method using a charged particle beam, there is a problem that, particularly when the substrate is insulating, the trajectory of the charged particle beam is bent due to an electric field generated by charging up the substrate, making it difficult to obtain a desired pattern. As a means for solving this problem, a technique is already known to be effective in which a conductive composition containing a conductive polymer is applied to the surface of a resist layer to form a coating film, and the surface of the resist layer is coated with the coating film to impart antistatic properties to the resist layer.
[0004] Polyaniline having acidic groups is known as a conductive polymer, and can exhibit conductivity without the addition of a dopant. Polyaniline having an acidic group can be obtained, for example, by polymerizing aniline having an acidic group with an oxidizing agent in the presence of a basic reaction promoter. However, the polyaniline having acidic groups obtained in this manner is obtained as a reaction mixture containing by-products such as raw material monomers (unreacted monomers) and decomposition products of the oxidizing agent (e.g., sulfate ions, etc.). In addition, the acidic groups of the polyaniline having acidic groups are easily hydrolyzed and unstable, and the acidic groups may be eliminated. In particular, when heat is applied to the polyaniline having acidic groups, the acidic groups tend to be eliminated or the polyaniline itself tends to be easily decomposed.
[0005] Therefore, when polyaniline with acidic groups is applied to a chemically amplified resist, when exposure, PEB treatment and development are performed with a conductive film formed on the resist layer, raw material monomers, decomposition products of polyaniline, detached acidic groups, sulfate ions which are decomposition products of oxidizing agents, etc. (hereinafter collectively referred to as "acidic substances") tend to migrate to the resist layer. As a result, the pattern shape tends to change and the sensitivity tends to fluctuate, affecting the resist layer. Specifically, when the resist layer is a positive type, if an acidic substance or the like migrates from the conductive film to the resist layer, the unexposed parts of the resist layer will dissolve during development, resulting in a decrease in the thickness of the resist layer, narrowing of the pattern, and a shift in sensitivity to the high sensitivity side.
[0006] In view of this, conductive compositions have been proposed which are excellent in conductivity and cause little film loss in the resist layer. For example, Patent Document 1 discloses a conductive composition containing a conductive polymer having an acidic group and a basic compound such as tetrabutylammonium hydroxide. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2014 / 017540 Summary of the Invention [Problem to be solved by the invention]
[0008] However, if the conductive composition contains low molecular weight components that can cause defects, the components may aggregate during film formation and appear as foreign matter in the coating film. In a coating film containing such foreign matter, problems such as line breaks may occur after drawing with an electron beam. Although the conductive composition described in Patent Document 1 can suppress the migration of acidic substances into the resist layer, there is still room for improvement in terms of reducing defect-causing components.
[0009] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a conductive composition and a method for producing the same that are less likely to produce foreign matter when formed into a coating film, as well as a conductor and a method for producing the same. Another object of the present invention is to provide a new conductive composition that differs from conventional compositions and a method for producing the same. [Means for solving the problem]
[0010] The present invention has the following aspects. [1] A conductive composition comprising a conductive polymer (A) having an acidic group and a basic compound (B), A conductive composition having an area ratio (X / Y) of 0.046 or less, as calculated by an evaluation method including the following steps (I) to (VI): (I) A step of preparing a test solution by dissolving the conductive composition in an eluent adjusted to have a pH of 10 or more, so that the solid content concentration of the conductive polymer (A) is 0.1 mass %. (II) A step of measuring the molecular weight distribution of the test solution using a polymer material evaluation device equipped with a gel permeation chromatograph to obtain a chromatogram. (III) A step of converting the retention time of the chromatogram obtained in the step (II) into a molecular weight (M) in terms of sodium polystyrene sulfonate. (IV) A step of determining the area (X) of a region having a molecular weight (M) of 300 to 3,300 in terms of the molecular weight (M) converted into sodium polystyrene sulfonate. (V) A step of determining the area (Y) of the entire region derived from the conductive polymer (A) in terms of the molecular weight (M) converted into sodium polystyrene sulfonate. (VI) A step of calculating the area ratio (X / Y) between the area (X) and the area (Y). [2] A conductive composition comprising a conductive polymer (A) having an acidic group and a basic compound (B), An electrically conductive composition having a ZS / ZR of 20 or less. wherein ZS is the maximum value of fluorescence intensity in the wavelength region of 320 to 420 nm when a fluorescence spectrum of a measurement solution obtained by diluting the conductive composition with water so that the solid content concentration of the conductive polymer (A) is 0.6 mass % is measured using a spectrofluorometer at an excitation wavelength of 230 nm; The ZR is the maximum value of Raman scattering intensity in the wavelength range of 380 to 420 nm when the fluorescence spectrum of water is measured at an excitation wavelength of 350 nm using a spectrofluorometer. [3] The conductive composition according to [1] or [2], further comprising a surfactant (C) and a solvent (D). [4] A conductor comprising a substrate and a coating film formed by applying the conductive composition according to any one of [1] to [3] onto at least one surface of the substrate. [5] A method for producing an electric conductor, comprising applying the conductive composition according to any one of [1] to [3] onto at least one surface of a substrate to form a coating film.
[0011] [6] a step of heating a mixed liquid containing the conductive polymer (A) having an acidic group and the basic compound (B); A step of purifying the mixed liquid after heating so that the area ratio (X / Y) calculated by an evaluation method including the following steps (i) to (vi) is 0.046 or less; The method for producing a conductive composition comprising the steps of: (i) A step of preparing a test solution by dissolving the purified mixed liquid in an eluent adjusted to have a pH of 10 or more so that the solid content concentration of the conductive polymer (A) is 0.1 mass %. (ii) A step of measuring the molecular weight distribution of the test solution using a polymer material evaluation device equipped with a gel permeation chromatograph to obtain a chromatogram. (iii) converting the retention time of the chromatogram obtained in the step (ii) into a molecular weight (M) in terms of sodium polystyrene sulfonate. (iv) A step of calculating the area (X) of a region having a molecular weight (M) of 300 to 3,300 in terms of the molecular weight (M) converted into sodium polystyrene sulfonate. (v) A step of determining the area (Y) of the entire region derived from the conductive polymer (A) in terms of the molecular weight (M) converted into sodium polystyrene sulfonate. (vi) A process of calculating the area ratio (X / Y) between the area (X) and the area (Y). [7] a step of heating a mixed liquid containing the conductive polymer (A) having an acidic group and the basic compound (B); purifying the heated mixture so that the ZS / ZR is 20 or less; The method for producing a conductive composition comprising the steps of: wherein ZS is the maximum value of fluorescence intensity in the wavelength region of 320 to 420 nm when a fluorescence spectrum of a measurement solution obtained by diluting the conductive composition with water so that the solid content concentration of the conductive polymer (A) is 0.6 mass % is measured using a spectrofluorometer at an excitation wavelength of 230 nm; The ZR is the maximum value of Raman scattering intensity in the wavelength range of 380 to 420 nm when the fluorescence spectrum of water is measured at an excitation wavelength of 350 nm using a spectrofluorometer. [8] A method for producing the conductive composition according to [6] or [7], comprising the step of adding a surfactant (C) and a solvent (D) to the purified mixed liquid. Effect of the Invention
[0012] According to the present invention, it is possible to provide a conductive composition which is less likely to generate foreign matter when formed into a coating film, a method for producing the same, and a conductor and a method for producing the same. Furthermore, according to the present invention, it is possible to provide a new conductive composition different from conventional compositions and a method for producing the same. [Brief description of the drawings]
[0013] [Figure 1] 1 is an example of a chromatogram obtained by gel permeation chromatography in step (II) of the evaluation method. [Diagram 2] Fluorescence spectra of Example 2 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below. The following embodiments are merely examples for explaining the present invention, and are not intended to limit the present invention to these embodiments. The present invention can be implemented in various forms without departing from the spirit of the present invention.
[0015] In the present invention, "conductive" means a 10 The surface resistance is determined by the potential difference between electrodes when a constant current is passed through them. In addition, in this specification, "solubility" means that 0.1 g or more of the substance dissolves uniformly in 10 g (liquid temperature 25° C.) of one or more of the following solvents: simple water, water containing at least one of a base and a basic salt, water containing an acid, and a mixture of water and a water-soluble organic solvent. Furthermore, "water solubility" means solubility in water with respect to the above solubility. In addition, in this specification, the term "acidic substance" refers to a substance having a negative charge, and specifically refers to raw material monomers of the conductive polymer (A), decomposition products of the conductive polymer (A), acidic groups (free acidic groups) released from the conductive polymer (A), and decomposition products of the oxidizing agent used in the production of the conductive polymer (A) (e.g., sulfate ions, etc.). In this specification, the term "terminal" in "terminal hydrophobic group" refers to a site other than the repeating units constituting the polymer. In addition, in this specification, the "mass average molecular weight" refers to the mass average molecular weight (converted into sodium polystyrene sulfonate) measured by gel permeation chromatography (GPC).
[0016] [Conductive composition] <First aspect> The conductive composition according to the first aspect of the present invention contains a conductive polymer (A) and a basic compound (B) described below. The conductive composition preferably further contains a surfactant (C) and a solvent (D) described below.
[0017] (Conductive Polymer (A)) The conductive polymer (A) has an acidic group. When the conductive polymer (A) has an acidic group, the water solubility is increased. As a result, the coatability of the conductive composition is improved, and a coating film of uniform thickness can be easily obtained. The conductive polymer having an acidic group is not particularly limited as long as it has at least one group selected from the group consisting of a sulfonic acid group and a carboxy group in the molecule and has the effects of the present invention, and known conductive polymers can be used. For example, JP-A-61-197633, JP-A-63-39916, JP-A-1-301714, JP-A-5-504153, JP-A-5-503953, JP-A-4-32848, JP-A-4-328181, JP-A-6-145386, JP-A-6-56987, JP-A-5-226238, JP-A-5-178989, and the like. Conductive polymers such as those disclosed in JP-A-6-293828, JP-A-7-118524, JP-A-6-32845, JP-A-6-87949, JP-A-6-256516, JP-A-7-41756, JP-A-7-48436, JP-A-4-268331, and JP-A-2014-65898 are preferred from the viewpoint of solubility.
[0018] Specific examples of the conductive polymer having an acidic group include π-conjugated conductive polymers containing, as a repeating unit, at least one selected from the group consisting of phenylenevinylene, vinylene, thienylene, pyrrolylene, phenylene, iminophenylene, isothianaphthene, furylene, and carbazolylene, the α- or β-position of which is substituted with at least one group selected from the group consisting of a sulfonic acid group and a carboxy group. In addition, when the π-conjugated conductive polymer contains at least one type of repeating unit selected from the group consisting of iminophenylene and carbazolylene, examples of the conductive polymer include a conductive polymer having, on a nitrogen atom of the repeating unit, at least one group selected from the group consisting of a sulfonic acid group and a carboxy group, or an alkyl group substituted with at least one group selected from the group consisting of a sulfonic acid group and a carboxy group, or an alkyl group containing an ether bond, on the nitrogen atom. Among these, from the viewpoints of electrical conductivity and solubility, a conductive polymer having, as a monomer unit, at least one selected from the group consisting of thienylene, pyrrolylene, iminophenylene, phenylenevinylene, carbazolylene, and isothianaphthene, the β-position of which is substituted with at least one group selected from the group consisting of a sulfonic acid group and a carboxy group, is preferably used.
[0019] From the viewpoint of exhibiting high electrical conductivity and solubility, the conductive polymer (A) is preferably a conductive polymer containing one or more monomer units selected from the group consisting of units represented by the following general formulas (1) to (4) in an amount of 20 to 100 mol % based on the total units (100 mol %) constituting the conductive polymer.
[0020] [ka]
[0021] [ka]
[0022] [ka]
[0023] [ka]
[0024] In formulas (1) to (4), X represents a sulfur atom or a nitrogen atom; 1 ~R 15 each independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 24 carbon atoms, a linear or branched alkoxy group having 1 to 24 carbon atoms, an acidic group, a hydroxyl group, a nitro group, a halogen atom (-F, -Cl, -Br or I), -N(R 16 ) 2 , -NHCOR 16 , -SR 16 , -OCOR 16 , -COOR 16 , -COR 16 , -CHO, or -CN. 16 represents an alkyl group having 1 to 24 carbon atoms, an aryl group having 6 to 24 carbon atoms, or an aralkyl group having 7 to 24 carbon atoms. However, R in general formula (1) 1 and R 2 At least one of R in general formula (2) 3 ~R 6 At least one of R in general formula (3) 7 ~R 10 At least one of R in general formula (4) 11 ~R 15 At least one of each is an acidic group or a salt thereof.
[0025] Here, the term "acidic group" refers to a sulfonic acid group (sulfo group) or a carboxylic acid group (carboxy group). The sulfonic acid group is in the acid form (-SO 3 H), or in the ionic state (-SO 3 - In addition, the sulfonic acid group may be a substituent (-R 17 SO 3 H) is also included. On the other hand, the carboxylic acid group may be present in either an acid form (-COOH) or an ionic form (-COO - In addition, the carboxylic acid group may be provided with a substituent (-R 17 COOH) are also included. R 17represents a linear or branched alkylene group having 1 to 24 carbon atoms, a linear or branched arylene group having 6 to 24 carbon atoms, or a linear or branched aralkylene group having 7 to 24 carbon atoms.
[0026] Salts of acidic groups include alkali metal salts, alkaline earth metal salts, ammonium salts, or substituted ammonium salts of sulfonic acid or carboxylic acid groups. Examples of the alkali metal salt include lithium sulfate, lithium carbonate, lithium hydroxide, sodium sulfate, sodium carbonate, sodium hydroxide, potassium sulfate, potassium carbonate, potassium hydroxide, and derivatives having a skeleton of these. Examples of the alkaline earth metal salt include magnesium salts and calcium salts. Examples of the substituted ammonium salt include aliphatic ammonium salts, saturated alicyclic ammonium salts, and unsaturated alicyclic ammonium salts. Examples of aliphatic ammonium salts include methylammonium, dimethylammonium, trimethylammonium, ethylammonium, diethylammonium, triethylammonium, methylethylammonium, diethylmethylammonium, dimethylethylammonium, propylammonium, dipropylammonium, isopropylammonium, diisopropylammonium, butylammonium, dibutylammonium, methylpropylammonium, ethylpropylammonium, methylisopropylammonium, ethylisopropylammonium, methylbutylammonium, ethylbutylammonium, tetramethylammonium, tetramethylolammonium, tetraethylammonium, tetra-n-butylammonium, tetra-sec-butylammonium, and tetra-t-butylammonium. Examples of the saturated alicyclic ammonium salt include piperidinium, pyrrolidinium, morpholinium, piperazinium, and derivatives having these skeletons. Examples of unsaturated alicyclic ammonium salts include pyridinium, α-picolinium, β-picolinium, γ-picolinium, quinolinium, isoquinolinium, pyrrolinium, and derivatives having these skeletons.
[0027] The conductive polymer (A) preferably has a unit represented by the above general formula (4) from the viewpoint of exhibiting high conductivity, and more preferably has a monomer unit represented by the following general formula (5) from the viewpoint of also having excellent solubility.
[0028] [ka]
[0029] In formula (5), R 18 ~R 21 each independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 24 carbon atoms, a linear or branched alkoxy group having 1 to 24 carbon atoms, an acidic group, a hydroxyl group, a nitro group, or a halogen atom (-F, -Cl, -Br, or I). 18 ~R 21 At least one of the groups is an acidic group or a salt thereof.
[0030] As the unit represented by the general formula (5), R 18 ~R 21 Among these, it is preferable that one of them is a linear or branched alkoxy group having 1 to 4 carbon atoms, one of the others is a sulfonic acid group, and the remaining are hydrogen.
[0031] From the viewpoint of excellent solubility in water and organic solvents regardless of pH, the conductive polymer (A) preferably contains 10 to 100 mol %, more preferably 50 to 100 mol %, and particularly preferably 100 mol % of units represented by the general formula (5) among all units (100 mol %) constituting the conductive polymer (A). From the viewpoint of excellent conductivity, the conductive polymer (A) preferably contains 10 or more units represented by the general formula (5) in one molecule.
[0032] In addition, in the conductive polymer (A), from the viewpoint of further improving solubility, the number of aromatic rings having acidic groups bonded to the total number of aromatic rings in the polymer is preferably 50% or more, more preferably 70% or more, even more preferably 80% or more, particularly preferably 90% or more, and most preferably 100%. The number of aromatic rings having acidic groups bonded thereto relative to the total number of aromatic rings in the polymer refers to a value calculated from the monomer charging ratio during the production of the conductive polymer (A).
[0033] In the conductive polymer (A), the substituents other than the acidic group on the aromatic ring of the monomer unit are preferably electron-donating groups from the viewpoint of imparting reactivity to the monomer. Specifically, alkyl groups having 1 to 24 carbon atoms, alkoxy groups having 1 to 24 carbon atoms, halogen groups (-F, -Cl, -Br or I) and the like are preferred. Among these, an alkoxy group having 1 to 24 carbon atoms is most preferred from the viewpoint of electron-donating ability.
[0034] Furthermore, the conductive polymer (A) may contain, as a constituent unit other than the unit represented by the general formula (5), one or more units selected from the group consisting of substituted or unsubstituted aniline, thiophene, pyrrole, phenylene, vinylene, divalent unsaturated groups, and divalent saturated groups, so long as the solubility, conductivity, and properties are not affected.
[0035] From the viewpoint of achieving high conductivity and solubility, the conductive polymer (A) is preferably a compound having a structure represented by the following general formula (6), and among the compounds having a structure represented by the following general formula (6), poly(2-sulfo-5-methoxy-1,4-iminophenylene) is particularly preferred.
[0036] [ka]
[0037] In formula (6), R 22 ~R 37 each independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 4 carbon atoms, a linear or branched alkoxy group having 1 to 4 carbon atoms, an acidic group, a hydroxyl group, a nitro group, or a halogen atom (-F, -Cl, -Br, or I). 22 ~R 37 At least one of the groups is an acidic group or a salt thereof. Furthermore, n represents the degree of polymerization. In the present invention, n is preferably an integer of 5 to 2,500.
[0038] From the viewpoint of improving electrical conductivity, it is desirable that at least a part of the acidic groups contained in the conductive polymer (A) is in a free acid form.
[0039] The weight average molecular weight (Mw) of the conductive polymer (A) is preferably 1000 to 1 million, more preferably 1500 to 800,000, even more preferably 2000 to 500,000, and particularly preferably 2000 to 100,000, in terms of electrical conductivity, solubility, and film-forming properties, as calculated by GPC using sodium polystyrene sulfonate. When the weight average molecular weight of the conductive polymer (A) is less than 1000, the solubility is excellent, but the electrical conductivity and film-forming properties may be insufficient. On the other hand, when the weight average molecular weight exceeds 1 million, the electrical conductivity is excellent, but the solubility may be insufficient. Here, the term "film-forming ability" refers to the ability to form a uniform film without repelling or the like, and can be evaluated by a method such as spin coating on glass.
[0040] The method for producing the conductive polymer (A) can be a known method, and is not particularly limited as long as it has the effect of the present invention. Specifically, examples of the method include a method of polymerizing a polymerizable monomer (raw material monomer) having any of the above-mentioned monomer units by various synthesis methods such as a chemical oxidation method, an electrolytic oxidation method, etc. As such a method, for example, the synthesis methods described in JP-A-7-196791 and JP-A-7-324132 can be applied. An example of a method for producing the conductive polymer (A) will be described below.
[0041] The conductive polymer (A) can be obtained, for example, by polymerizing raw material monomers using an oxidizing agent in the presence of a basic reaction aid. Specific examples of the raw material monomer include at least one selected from the group consisting of acidic group-substituted aniline, its alkali metal salt, alkaline earth metal salt, ammonium salt and substituted ammonium salt. Examples of the acidic group-substituted aniline include sulfonic acid group-substituted aniline having a sulfonic acid group as the acidic group. Representative examples of sulfone group-substituted anilines include aminobenzenesulfonic acids. Specifically, o-, m-, and p-aminobenzenesulfonic acid, aniline-2,6-disulfonic acid, aniline-2,5-disulfonic acid, aniline-3,5-disulfonic acid, aniline-2,4-disulfonic acid, and aniline-3,4-disulfonic acid are preferably used.
[0042] Examples of sulfone group-substituted anilines other than aminobenzenesulfonic acids include alkyl group-substituted aminobenzenesulfonic acids such as methylaminobenzenesulfonic acid, ethylaminobenzenesulfonic acid, n-propylaminobenzenesulfonic acid, isopropylaminobenzenesulfonic acid, n-butylaminobenzenesulfonic acid, sec-butylaminobenzenesulfonic acid, and t-butylaminobenzenesulfonic acid; alkoxy group-substituted aminobenzenesulfonic acids such as methoxyaminobenzenesulfonic acid, ethoxyaminobenzenesulfonic acid, and propoxyaminobenzenesulfonic acid; hydroxy group-substituted aminobenzenesulfonic acids; nitro group-substituted aminobenzenesulfonic acids; and halogen-substituted aminobenzenesulfonic acids such as fluoroaminobenzenesulfonic acid, chloroaminobenzenesulfonic acid, and bromoaminobenzenesulfonic acid. Among these, alkyl group-substituted aminobenzenesulfonic acids, alkoxy group-substituted aminobenzenesulfonic acids, hydroxy group-substituted aminobenzenesulfonic acids, and halogen-substituted aminobenzenesulfonic acids are preferred in that they give a conductive polymer (A) that is particularly excellent in conductivity and solubility, and alkoxy group-substituted aminobenzenesulfonic acids, their alkali metal salts, ammonium salts, and substituted ammonium salts are particularly preferred in that they are easy to produce. These sulfonate group-substituted anilines may be used alone or in combination of two or more in any desired ratio.
[0043] Examples of the basic reaction auxiliary include inorganic bases such as sodium hydroxide, potassium hydroxide, and lithium hydroxide; ammonia; aliphatic amines such as methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylmethylamine, ethyldimethylamine, and diethylmethylamine; cyclic saturated amines; and cyclic unsaturated amines such as pyridine, α-picoline, β-picoline, γ-picoline, and quinoline. Among these, inorganic bases, aliphatic amines, and cyclic unsaturated amines are preferred, and inorganic bases are more preferred. These basic reaction auxiliaries may be used alone or in combination of two or more kinds in any desired ratio.
[0044] The oxidizing agent is not limited as long as it has a standard electrode potential of 0.6 V or more, and examples thereof include peroxodisulfuric acid, ammonium peroxodisulfate, sodium peroxodisulfate, potassium peroxodisulfate, and other peroxodisulfates; hydrogen peroxide, and the like. These oxidizing agents may be used alone or in combination of two or more kinds in any desired ratio.
[0045] Examples of the polymerization method include a method of dropping a mixed solution of raw material monomer and basic reaction auxiliary into an oxidizing agent solution, a method of dropping an oxidizing agent solution into a mixed solution of raw material monomer and basic reaction auxiliary, and a method of dropping a mixed solution of raw material monomer and basic reaction auxiliary and an oxidizing agent solution simultaneously into a reaction vessel or the like.
[0046] After the polymerization, the solvent is usually filtered off using a filter such as a centrifugal separator, etc. If necessary, the filtrate is washed with a washing liquid and then dried to obtain the conductive polymer (A). The acidic group of the conductive polymer (A) thus obtained is a group selected from the group consisting of free acid, alkali metal salt, alkaline earth metal salt, ammonium salt and substituted ammonium salt, and therefore it is possible to obtain a polymer having not only a single group but also a mixture of these groups. For example, when sodium hydroxide is used as a basic reaction aid during polymerization, most of the acidic groups in the conductive polymer (A) are in the form of sodium salts. When ammonia is used as a basic reaction aid, most of the acidic groups in the conductive polymer (A) are in the form of ammonium salts, when trimethylamine is used, most of the acidic groups in the conductive polymer (A) are in the form of trimethylammonium salts, and when quinoline is used, most of the acidic groups in the conductive polymer (A) are in the form of quinolinium salts.
[0047] The conductive polymer (A) thus obtained may contain low molecular weight components such as oligomers, acidic substances, and basic substances (basic reaction aids and ammonium ions which are decomposition products of oxidizing agents) due to side reactions. These low molecular weight components are factors that inhibit conductivity.
[0048] Therefore, it is preferable to purify the conductive polymer (A) to remove low molecular weight components. The method for purifying the conductive polymer (A) is not particularly limited, and any method can be used, such as an ion exchange method, acid washing in a protonic acid solution, removal by heat treatment, neutralization precipitation, etc. Among these, the ion exchange method is particularly effective from the viewpoint of easily obtaining a conductive polymer (A) with high purity. By using the ion exchange method, basic substances that exist in a state of forming a salt with the acidic group of the conductive polymer (A), acidic substances, etc. can be effectively removed, and a conductive polymer (A) with high purity can be obtained.
[0049] Examples of the ion exchange method include column or batch treatment using ion exchange resins such as cation exchange resins or anion exchange resins; and electrodialysis. When purifying the conductive polymer (A) by an ion exchange method, it is preferable to dissolve the reaction mixture obtained by polymerization in an aqueous medium to a desired solid concentration, prepare a polymer solution, and then contact the solution with an ion exchange resin. Examples of the aqueous medium include the same as the solvent (D) described below. The concentration of the conductive polymer (A) in the polymer solution is preferably from 0.1 to 20% by mass, more preferably from 0.1 to 10% by mass, from the viewpoints of industrial feasibility and purification efficiency.
[0050] In the case of an ion exchange method using an ion exchange resin, the amount of sample liquid relative to the ion exchange resin is preferably up to 10 times the volume of the ion exchange resin, more preferably up to 5 times the volume, for example, in the case of a polymer solution with a solid content concentration of 5% by mass. Examples of cation exchange resins include "Amberlite IR-120B" manufactured by Organo Corporation. Examples of anion exchange resins include "Amberlite IRA410" manufactured by Organo Corporation.
[0051] The conductive polymer (A) purified in this manner has oligomers, acidic substances, basic substances, etc. sufficiently removed, and therefore exhibits superior conductivity. The purified conductive polymer (A) is in a state of being dispersed or dissolved in an aqueous medium. Therefore, a solid conductive polymer (A) can be obtained by removing the entire aqueous medium using an evaporator or the like, but the conductive polymer (A) may be used in the production of a conductive composition while remaining dispersed or dissolved in an aqueous medium.
[0052] The content of the conductive polymer (A) is preferably from 0.1 to 5 mass %, more preferably from 0.2 to 3 mass %, and even more preferably from 0.5 to 2 mass %, based on the total mass of the conductive composition. The content of the conductive polymer (A) is preferably 50 to 99.9 mass%, more preferably 80 to 99.9 mass%, and even more preferably 95 to 99.9 mass%, based on the total mass of the solid content of the conductive composition. The solid content of the conductive composition is the remainder after removing the solvent (D) from the conductive composition. When the content of the conductive polymer (A) is within the above range, a better balance between the coatability of the conductive composition and the conductivity of the coating film formed from the conductive composition is achieved.
[0053] (Basic Compound (B)) It is believed that the conductive composition contains a basic compound (B), and thus the basic compound (B) acts efficiently on the acidic groups in the conductive polymer (A), thereby making it possible to enhance the stability of the conductive polymer (A). Here, the term "efficiently acting on the acidic groups in the conductive polymer (A)" means that the conductive polymer (A) can be stably neutralized, and a stable salt is formed between the acidic groups of the conductive polymer (A) and the basic compound (B). That is, the conductive polymer (A) is neutralized with the basic compound (B). As a result, the destabilization of the acidic groups of the conductive polymer (A) due to hydrolysis in the conductive composition can be suppressed, and the acidic groups are less likely to be released. In addition, the decomposition of the conductive polymer (A) itself can be suppressed by forming a stable salt between the acidic groups of the conductive polymer (A) and the basic compound (B). In addition, the basic compound (B) also forms a stable salt with the decomposition product (e.g., sulfate ion, etc.) of the oxidizing agent used in the production of the conductive polymer (A). Therefore, the generation of acidic groups derived from the conductive polymer (A) and sulfate ions derived from the oxidizing agent in the conductive composition can be suppressed. Furthermore, the content of decomposition products of the conductive polymer (A) in the conductive composition can also be reduced. Therefore, particularly in a pattern formation method using a charged particle beam and a chemically amplified resist, migration of acidic substances and the like from the conductive film to the resist layer is suppressed, and the effects of film loss of the resist layer and the like can be suppressed.
[0054] The basic compound (B) is not particularly limited as long as it is a compound having basicity, and examples thereof include the following quaternary ammonium compound (b-1), basic compound (b-2), and basic compound (b-3). Quaternary ammonium compound (b-1): A quaternary ammonium compound in which at least one of the four substituents bonded to the nitrogen atom is a hydrocarbon group having three or more carbon atoms. Basic compound (b-2): A basic compound having one or more nitrogen atoms (excluding quaternary ammonium compounds (b-1) and basic compounds (b-3)). Basic compound (b-3): A basic compound having a basic group and two or more hydroxyl groups in the same molecule and having a melting point of 30°C or higher.
[0055] In the quaternary ammonium compound (b-1), the nitrogen atom to which the four substituents are bonded is a nitrogen atom of a quaternary ammonium ion. In the quaternary ammonium compound (b-1), examples of the hydrocarbon group bonded to the nitrogen atom of the quaternary ammonium ion include an alkyl group, an aralkyl group, and an aryl group. Examples of the quaternary ammonium compound (b-1) include tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetrapentylammonium hydroxide, tetrahexylammonium hydroxide, and benzyltrimethylammonium hydroxide.
[0056] Examples of the basic compound (b-2) include ammonia, pyridine, triethylamine, 4-dimethylaminopyridine, 4-dimethylaminomethylpyridine, 3,4-bis(dimethylamino)pyridine, 1,5-diazabicyclo[4.3.0]-5-nonene (DBN), 1,8-diazabicyclo[5.4.0]-7-undecene (DBU), and derivatives thereof.
[0057] In the basic compound (b-3), examples of the basic group include basic groups defined as Arrhenius bases, Bronsted bases, Lewis bases, etc. Specific examples include ammonia, etc. The hydroxyl group may be in the -OH state or may be protected by a protective group. Examples of the protective group include an acetyl group; a silyl group such as a trimethylsilyl group or a t-butyldimethylsilyl group; an acetal-type protective group such as a methoxymethyl group, an ethoxymethyl group, or a methoxyethoxymethyl group; a benzoyl group; and an alkoxide group. Examples of the basic compound (b-3) include 2-amino-1,3-propanediol, tris(hydroxymethyl)aminomethane, 2-amino-2-methyl-1,3-propanediol, 2-amino-2-ethyl-1,3-propanediol, 3-[N-tris(hydroxymethyl)methylamino]-2-hydroxypropanesulfonic acid, and N-tris(hydroxymethyl)methyl-2-aminoethanesulfonic acid.
[0058] These basic compounds may be used either alone or as a mixture of two or more kinds in any desired ratio. Among these, it is preferable to contain at least one selected from the group consisting of quaternary ammonium compounds (b-1) and basic compounds (b-2), since they are likely to form a salt with the acidic groups of the conductive polymer (A) and are excellent in the effect of stabilizing the acidic groups and suppressing the influence of acidic substances from the coating film on the resist pattern.
[0059] The content of the basic compound (B) is preferably 0.1 to 1 mol equivalent, more preferably 0.1 to 0.9 mol equivalent, per mol of units having an acidic group among the units constituting the conductive polymer (A) from the viewpoint of further improving the coatability of the conductive composition, and is particularly preferably 0.25 to 0.85 mol equivalent, from the viewpoint of excellent retention of performance as a conductive film and further stabilizing the acidic group in the conductive polymer (A).
[0060] (Surfactant (C)) If the conductive composition contains a surfactant, the coating properties of the conductive composition are improved when the composition is applied to the surface of a substrate or a resist layer. Examples of the surfactant include anionic surfactants, cationic surfactants, amphoteric surfactants, nonionic surfactants, etc. These surfactants may be used alone or in combination of two or more kinds in any ratio.
[0061] Examples of anionic surfactants include sodium octanoate, sodium decanoate, sodium laurate, sodium myristate, sodium palmitate, sodium stearate, perfluorononanoic acid, sodium N-lauroyl sarcosine, sodium cocoyl glutamate, alpha sulfo fatty acid methyl ester salts, sodium lauryl sulfate, sodium myristyl sulfate, sodium laureth sulfate, sodium polyoxyethylene alkylphenol sulfonate, ammonium lauryl sulfate, lauryl phosphoric acid, sodium lauryl phosphate, and potassium lauryl phosphate.
[0062] Examples of cationic surfactants include tetramethylammonium chloride, tetramethylammonium hydroxide, tetrabutylammonium chloride, dodecyldimethylbenzylammonium chloride, alkyltrimethylammonium chloride, octyltrimethylammonium chloride, decyltrimethylammonium chloride, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, cetyltrimethylammonium chloride, stearyltrimethylammonium chloride, alkyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, benzyltrimethylammonium chloride, benzyltriethylammonium chloride, benzalkonium chloride, benzalkonium bromide, benzethonium chloride, dialkyldimethylammonium chloride, didecyldimethylammonium chloride, distearyldimethylammonium chloride, monomethylamine hydrochloride, dimethylamine hydrochloride, trimethylamine hydrochloride, butylpyridinium chloride, dodecylpyridinium chloride, and cetylpyridinium chloride.
[0063] Examples of amphoteric surfactants include lauryl dimethylaminoacetate betaine, stearyl dimethylaminoacetate betaine, dodecylaminomethyl dimethylsulfopropyl betaine, octadecylaminomethyl dimethylsulfopropyl betaine, cocamidopropyl betaine, cocamidopropyl hydroxysultaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, sodium lauroyl glutamate, potassium lauroyl glutamate, lauroyl methyl-β-alanine, lauryl dimethylamine-N-oxide, and oleyl dimethylamine N-oxide.
[0064] Examples of nonionic surfactants include glyceryl laurate, glyceryl monostearate, sorbitan fatty acid esters, sucrose fatty acid esters, polyoxyethylene alkyl ethers, pentaethylene glycol monododecyl ether, octaethylene glycol monododecyl ether, polyoxyethylene alkyl phenyl ethers, octylphenol ethoxylate, nonylphenol ethoxylate, polyoxyethylene polyoxypropylene glycol, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene hexyltan fatty acid esters, sorbitan fatty acid ester polyethylene glycol, lauric acid diethanolamide, oleic acid diethanolamide, stearic acid diethanolamide, octyl glucoside, decyl glucoside, lauryl glucoside, cetanol, stearyl alcohol, and oleyl alcohol.
[0065] In addition to the above, a water-soluble polymer having a nitrogen-containing functional group and a terminal hydrophobic group may be used as the nonionic surfactant. Unlike conventional surfactants, this water-soluble polymer has surface activity due to the main chain portion (hydrophilic portion) having a nitrogen-containing functional group and the terminal hydrophobic group portion, and is highly effective in improving coatability. Therefore, excellent coatability can be imparted to the conductive composition without using other surfactants in combination. Moreover, this water-soluble polymer does not contain acids or bases, and is unlikely to produce by-products due to hydrolysis, so that it has particularly little adverse effect on the resist layer, etc.
[0066] From the viewpoint of solubility, the nitrogen-containing functional group is preferably an amide group. Examples of the terminal hydrophobic group include an alkyl group, an aralkyl group, an aryl group, an alkoxy group, an aralkyloxy group, an aryloxy group, an alkylthio group, an aralkylthio group, an arylthio group, a primary or secondary alkylamino group, an aralkylamino group, an arylamino group, etc. Among these, an alkylthio group, an aralkylthio group, and an arylthio group are preferred. The terminal hydrophobic group preferably has 3 to 100 carbon atoms, more preferably 5 to 50 carbon atoms, and particularly preferably 7 to 30 carbon atoms. The number of terminal hydrophobic groups in the water-soluble polymer is not particularly limited. When the water-soluble polymer has two or more terminal hydrophobic groups in the same molecule, the terminal hydrophobic groups may be the same or different.
[0067] As the water-soluble polymer, a compound having a main chain structure which is a homopolymer of a vinyl monomer having a nitrogen-containing functional group, or a copolymer of a vinyl monomer having a nitrogen-containing functional group and a vinyl monomer not having a nitrogen-containing functional group (other vinyl monomer), and having a hydrophobic group at a site other than the repeating units constituting the polymer, is preferred. Examples of vinyl monomers having nitrogen-containing functional groups include acrylamide and its derivatives, heterocyclic monomers having nitrogen-containing functional groups, and the like, among which those having amide bonds are preferred.Specific examples include acrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropylacrylamide, t-butylacrylamide, diacetoneacrylamide, N,N'-methylenebisacrylamide, N-vinyl-N-methylacrylamide, N-vinylpyrrolidone, N-vinylcaprolactam, and the like.Among these, acrylamide, N-vinylpyrrolidone, N-vinylcaprolactam, and the like are particularly preferred from the viewpoint of solubility. The other vinyl monomer is not particularly limited as long as it is capable of copolymerizing with a vinyl monomer having a nitrogen-containing functional group, and examples thereof include styrene, acrylic acid, vinyl acetate, and long-chain α-olefins.
[0068] The method of introducing a terminal hydrophobic group into a water-soluble polymer is not particularly limited, but it is usually preferable to introduce it by selecting a chain transfer agent during vinyl polymerization.In this case, the chain transfer agent is not particularly limited as long as it is a group containing a hydrophobic group such as an alkyl group, an aralkyl group, an aryl group, an alkylthio group, an aralkylthio group, or an arylthio group that is introduced to the end of the obtained polymer.For example, when obtaining a water-soluble polymer having an alkylthio group, an aralkylthio group, or an arylthio group as a terminal hydrophobic group, it is preferable to carry out vinyl polymerization using a chain transfer agent having a hydrophobic group corresponding to these terminal hydrophobic groups, specifically thiol, disulfide, thioether, etc.
[0069] The main chain portion of the water-soluble polymer is water-soluble and has a nitrogen-containing functional group. The number of units (degree of polymerization) of the main chain portion in one molecule is preferably 2 to 1000, more preferably 3 to 1000, and particularly preferably 5 to 10. If the number of units of the main chain portion having a nitrogen-containing functional group is too large, the surface activity tends to decrease. The molecular weight ratio (mass average molecular weight of main chain portion / mass average molecular weight of terminal hydrophobic group portion) of the water-soluble polymer to the main chain portion (e.g., alkyl group, aralkyl group, aryl group, alkylthio group, aralkylthio group, arylthio group, etc.) is preferably 0.3 to 170.
[0070] Of the above surfactants, nonionic surfactants are preferred as the surfactant (C) since they have little effect on the resist layer.
[0071] The content of the surfactant (C) is preferably 5 to 80 parts by mass, more preferably 10 to 70 parts by mass, and even more preferably 10 to 60 parts by mass, when the total of the conductive polymer (A), the basic compound (B), and the surfactant (C) is 100 parts by mass. When the content of the surfactant (C) is within the above range, the coatability of the conductive composition to the resist layer is further improved.
[0072] (Solvent (D)) The solvent (D) is not particularly limited as long as it is a solvent that can dissolve the conductive polymer (A), the basic compound (B), and the surfactant (C) and has the effects of the present invention. Examples of the solvent include water, an organic solvent, and a mixed solvent of water and an organic solvent. Examples of water include tap water, ion-exchanged water, pure water, and distilled water. Examples of organic solvents include alcohols such as methanol, ethanol, isopropyl alcohol, propyl alcohol, butanol, ketones such as acetone, ethyl isobutyl ketone, ethylene glycols such as ethylene glycol, ethylene glycol methyl ether, propylene glycols such as propylene glycol, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, propylene glycol propyl ether, amides such as dimethylformamide, dimethylacetamide, pyrrolidones such as N-methylpyrrolidone, N-ethylpyrrolidone, etc. Any one of these organic solvents may be used alone, or two or more of them may be mixed in any ratio and used. When a mixed solvent of water and an organic solvent is used as the solvent (D), the mass ratio thereof (water / organic solvent) is preferably 1 / 100 to 100 / 1, and more preferably 2 / 100 to 100 / 2.
[0073] The content of the solvent (D) is preferably 1 to 99 mass%, more preferably 10 to 98 mass%, and even more preferably 50 to 98 mass%, based on the total mass of the conductive composition. When the content of the solvent (D) is within the above range, the coating property is further improved. In addition, when the conductive polymer (A) is used in a state in which it is dispersed or dissolved in an aqueous medium after purification or the like (hereinafter, the conductive polymer (A) in this state is also referred to as a "conductive polymer solution"), the aqueous medium derived from the conductive polymer solution is also included in the content of the solvent (D) in the conductive composition.
[0074] (optional ingredient) The conductive composition may contain components (optional components) other than the conductive polymer (A), the basic compound (B), the surfactant (C) and the water (D) as necessary. Examples of optional components include pigments, antifoaming agents, ultraviolet absorbers, antioxidants, heat resistance improvers, leveling agents, sagging prevention agents, matting agents, and preservatives.
[0075] (Physical Properties) The conductive composition according to the first aspect of the present invention satisfies the following condition 1. Condition 1: The area ratio (X / Y) calculated by an evaluation method including the following steps (I) to (VI) is 0.046 or less. (I) A step of preparing a test solution by dissolving the conductive composition in an eluent adjusted to have a pH of 10 or more, so that the solid content concentration of the conductive polymer (A) is 0.1 mass %. (II) A step of measuring the molecular weight distribution of the test solution using a polymer material evaluation device equipped with a gel permeation chromatograph to obtain a chromatogram. (III) A step of converting the retention time of the chromatogram obtained in the step (II) into a molecular weight (M) in terms of sodium polystyrene sulfonate. (IV) A step of determining the area (X) of a region having a molecular weight (M) of 300 to 3,300 in terms of the molecular weight (M) converted into sodium polystyrene sulfonate. (V) A step of determining the area (Y) of the entire region derived from the conductive polymer (A) in terms of the molecular weight (M) converted into sodium polystyrene sulfonate. (VI) A step of calculating the area ratio (X / Y) between the area (X) and the area (Y).
[0076] Step (I) is a step of preparing a test solution by dissolving the conductive composition in an eluent so that the solid content concentration of the conductive polymer (A) becomes 0.1 mass %. The eluent is a liquid in which a solute is dissolved in a solvent, such as water, acetonitrile, alcohol (e.g., methanol, ethanol), dimethylformamide, dimethylsulfoxide, and mixtures thereof. Examples of the solute include sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, trisodium phosphate, disodium hydrogen phosphate, glycine, sodium hydroxide, potassium chloride, and boric acid.
[0077] The pH of the eluent used in step (I) is 10 or more. If the pH is less than 10, the quantitative value may fluctuate. By using an eluent with a pH of 10 or more, stable measurement results can be obtained. The eluent having a pH of 10 or higher can be prepared, for example, as follows. First, water (ultrapure water) and methanol are mixed in a volume ratio of water:methanol = 8:2 to obtain a mixed solvent. Next, sodium carbonate and sodium bicarbonate are added to the obtained mixed solvent so that the solid concentrations are 20 mmol / L and 30 mmol / L, respectively, to obtain an eluent. The eluate thus obtained has a pH of 10.8 at 25°C. The pH of the eluent was measured using a pH meter while the temperature of the eluent was kept at 25°C.
[0078] The method for preparing an eluent having a pH of 10 or more is not limited to the above-mentioned method. For example, a mixed solvent of water and methanol (water:methanol=8:2) may be used to separately prepare sodium carbonate with a solid concentration of 20 mmol / L and sodium hydrogen carbonate with a solid concentration of 30 mmol / L, and then these may be mixed to prepare the eluent.
[0079] The conductive composition may be added in a solid state to the eluent and dissolved therein, or may be added to the eluent in a state containing the solvent (D), i.e., in a liquid state, so long as the solid concentration of the conductive polymer (A) when added to the eluent is 0.1% by mass. If the solid concentration of the conductive polymer (A) in the test solution is 0.1% by mass, the pH buffering effect of the eluent is sufficiently exerted, and stable measurement results can be obtained. In addition, when using a conductive composition containing a solvent (D), the solid content concentration of the conductive composition is not particularly limited as long as the solid content concentration of the conductive polymer (A) is 0.1 mass% when added to the eluent, but is preferably 1.0 mass% or more. If the solid content concentration of the conductive composition is less than 1.0 mass%, the pH buffering effect of the eluent does not work sufficiently when added to the eluent, and the pH of the test solution becomes less than 10, causing the quantitative value to fluctuate, making it difficult to obtain stable measurement results.
[0080] Step (II) is a step of measuring the molecular weight distribution of the test solution by gel permeation chromatography (GPC) using a polymer material evaluation device. The polymer material evaluation device is equipped with a gel permeation chromatograph, and can separate and analyze compounds (polymers, oligomers, monomers) based on their molecular weight. The gel permeation chromatograph is connected to detectors such as a photodiode array detector and a UV detector. In step (II), a chromatogram such as that shown in FIG. 1 can be obtained by GPC. In the chromatogram shown in FIG. 1, the vertical axis represents absorbance and the horizontal axis represents retention time, with high molecular weight components being detected at relatively short retention times and low molecular weight components being detected at relatively long retention times.
[0081] Step (III) is a step of converting the retention time of the chromatogram obtained in step (II) into a molecular weight (M) in terms of sodium polystyrene sulfonate. Specifically, the peak top molecular weight is 206, 4300、6800、17000、32000、77000、15000、2600000 As in the case of the test solution, each standard sample is dissolved in an eluent so that the solid content concentration is 0.05 mass%, except for the standard sample with a peak top molecular weight of 206, which has a solid content concentration of 0.0025 mass%, to prepare a standard solution. Then, the relationship between retention time and molecular weight for each standard solution is determined by GPC, and a calibration curve is prepared. From the calibration curve, the retention time of the chromatogram obtained in step (II) is converted into the molecular weight (M) in terms of sodium polystyrene sulfonate.
[0082] Step (IV) is a step of determining the area (X) of a region having a molecular weight (M) of 300 to 3300 as shown in FIG. 1, for example, in terms of the molecular weight (M) calculated as sodium polystyrene sulfonate. Moreover, the step (V) is a step for determining the area (Y) of the entire region derived from the conductive polymer (A). Step (VI) is a step of determining the area ratio (X / Y) between area (X) and area (Y).
[0083] The conductive composition according to the first embodiment of the present invention has an area ratio (X / Y) calculated by the above-mentioned evaluation method, i.e., the ratio of the area (X) of the region having a molecular weight (M) of 300 to 3300 to the area (Y) of the entire region derived from the conductive polymer (A) is 0.046 or less. If the area ratio (X / Y) is 0.046 or less, the generation of foreign matter in the coating film formed from the conductive composition can be suppressed. The reason for this is considered to be as follows.
[0084] As described above, by including the basic compound (B) in the conductive composition, the conductive polymer (A) is neutralized with the basic compound (B), and the generation of acidic groups detached from the conductive polymer (A) in the conductive composition and decomposition products of the oxidizing agent (e.g., sulfate ions, etc.) can be suppressed. In addition, the content of decomposition products of the conductive polymer (A) in the conductive composition can also be reduced. However, as will be described in detail later, when the conductive polymer (A) is neutralized with the basic compound (B), heating is performed to promote neutralization. As a result, low molecular weight components are generated. Since these low molecular weight components are hydrophobic substances, they hinder the uniformity of the film and cause a decrease in conductivity. In addition, it is believed that the low molecular weight components aggregate during film formation and are generated on the coating film as foreign matter. In other words, the low molecular weight components are defect-causing components.
[0085] The area (X) is the area of the region where the molecular weight (M) is 300 to 3300, and low molecular weight components that cause foreign matter are mainly present in this region. If the area ratio (X / Y) is 0.046 or less, the proportion of low molecular weight components contained in the conductive composition is small, so that foreign matter is less likely to occur in the coating film formed from the conductive composition. The smaller the area ratio (X / Y) is, the smaller the proportion of low molecular weight components contained in the conductive composition. Therefore, the smaller the area ratio (X / Y) is, the more preferable it is, specifically, 0.040 or less is preferable. The lower limit of the area ratio (X / Y) is below the detection limit, and for example, the area ratio (X / Y) is preferably 0.001 or more. That is, the area ratio (X / Y) is 0.046 or less, preferably 0.001 to 0.046, and more preferably 0.001 to 0.040.
[0086] In order to obtain a conductive composition having an area ratio (X / Y) of 0.046 or less, for example, a purification step may be introduced in the production of the conductive composition. An example of a method for producing the conductive composition will now be described.
[0087] (Manufacturing method) The method for producing the conductive composition of the present embodiment includes a step of heat-treating a mixed liquid containing a conductive polymer (A) and a basic compound (B) (heating step), and a step of purifying the mixed liquid after heating (purification step) so that the area ratio (X / Y) calculated by an evaluation method including the following steps (i) to (vi) is 0.046 or less. (i) A step of preparing a test solution by dissolving the purified mixed liquid in an eluent adjusted to have a pH of 10 or more so that the solid content concentration of the conductive polymer (A) is 0.1 mass %. (ii) A step of measuring the molecular weight distribution of the test solution using a polymer material evaluation device equipped with a gel permeation chromatograph to obtain a chromatogram. (iii) converting the retention time of the chromatogram obtained in the step (ii) into a molecular weight (M) in terms of sodium polystyrene sulfonate. (iv) A step of calculating the area (X) of a region having a molecular weight (M) of 300 to 3,300 in terms of the molecular weight (M) converted into sodium polystyrene sulfonate. (v) A step of determining the area (Y) of the entire region derived from the conductive polymer (A) in terms of the molecular weight (M) converted into sodium polystyrene sulfonate. (vi) A process of calculating the area ratio (X / Y) between the area (X) and the area (Y).
[0088] The heating step is a step of heat-treating a mixed liquid containing the conductive polymer (A) and the basic compound (B). As the conductive polymer (A), it is preferable to use a conductive polymer (A) that has been purified during the production of the conductive polymer (A). The purified conductive polymer (A) is obtained in the form of a conductive polymer solution as described above. Therefore, a mixed solution is obtained by adding a basic compound (B) to the conductive polymer solution. If necessary, a solvent (D) may be added to the obtained mixed solution to dilute it. When a solid conductive polymer (A) is used, it is preferable to previously prepare a conductive polymer solution by mixing the solid conductive polymer (A) with the solvent (D), and then add the basic compound (B) to the obtained conductive polymer solution. The method of mixing each component is not particularly limited, and it is sufficient that the conductive polymer (A) and the basic compound (B) are mixed uniformly in the solvent (D). Examples of the mixing method include a method of stirring using a stirring rod, a stirrer, a shaker, etc. depending on the volume to be dissolved. In this specification, a mixed liquid containing the conductive polymer (A) and the basic compound (B) is also referred to as a "conductive polymer-containing liquid."
[0089] When the conductive polymer (A) comes into contact with the basic compound (B), a neutralization reaction takes place. This neutralization reaction takes place at room temperature, but the reaction is slow. Therefore, in the heating step, the mixed liquid containing the conductive polymer (A) and the basic compound (B) is heated to cause the neutralization reaction to proceed. Here, "room temperature" refers to 25°C. In this specification, the heating step is also referred to as a "neutralization step."
[0090] The heating temperature in the heating step is preferably 40° C. or higher from the viewpoint of stirring efficiency, and more preferably 60 to 80° C. from the viewpoint of the concentration of the acidic substance and the stability over time of the electrical conductivity.
[0091] The heating method in the heating step is not particularly limited, and the temperature of the mixed solution containing the conductive polymer (A) and the basic compound (B) may be maintained at a predetermined temperature for a certain period of time. For example, the conductive polymer solution may be heated at a predetermined temperature after adding the basic compound (B), or the conductive polymer solution may be heated to a predetermined temperature and then added with the basic compound (B).
[0092] The heating step neutralizes the conductive polymer (A) with the basic compound (B), that is, a stable salt is formed between the acidic group of the conductive polymer (A) and the basic compound (B).
[0093] The purification step is a step of purifying the heated mixture so that the area ratio (X / Y) calculated by the evaluation method including the above steps (i) to (vi) is 0.046 or less. In this specification, the mixed liquid after heating and before purification is also referred to as an "unpurified mixed liquid".
[0094] Step (i) is a step of preparing a test solution by dissolving the purified mixed liquid, i.e., the purified conductive polymer-containing liquid, in an eluent so that the solid content concentration of the conductive polymer (A) becomes 0.1 mass %. The eluent is the same as the eluent used in the above-mentioned step (I). The solid content of the purified mixture is not particularly limited, but is preferably 1.0% by mass or more. If the solid content of the purified mixture is less than 1.0% by mass, the pH buffering effect of the eluent does not work sufficiently when the mixture is added to the eluent, and the pH of the test solution becomes less than 10, causing fluctuations in the quantitative value and making it difficult to obtain stable measurement results. Steps (ii) to (vi) are the same as steps (II) to (VI) described above.
[0095] Examples of methods for purifying the unpurified mixed liquid so that the area ratio (X / Y) is 0.046 or less include membrane filtration, anion exchange, and contact with an adsorbent.
[0096] The filtration membrane used in the membrane filtration method is preferably a permeable membrane, and in consideration of removing low molecular weight components, a microfiltration membrane or an ultrafiltration membrane is particularly preferred. Examples of materials for the microfiltration membrane include organic membranes such as polyethylene (PE), tetrafluoroethylene (PTFE), polypropylene (PP), cellulose acetate (CA), polyacrylonitrile (PAN), polyimide (PI), polysulfone (PS), polyethersulfone (PES), nylon (Ny), etc. Nylon and polyethylene are particularly preferred from the viewpoint of excellent solvent resistance. The filter structure of the microfiltration membrane is not particularly limited as long as it is a material that is commonly used for microfiltration membranes, and examples thereof include a flat membrane pleated type and a hollow fiber type.
[0097] The material of the ultrafiltration membrane is not particularly limited as long as it is a material that is commonly used for ultrafiltration membranes, and examples thereof include organic membranes such as cellulose, cellulose acetate, polysulfone, polypropylene, polyester, polyethersulfone, polyvinylidene fluoride, etc., inorganic membranes such as ceramics, organic-inorganic hybrid membranes, etc. Ceramic membranes are particularly preferred from the viewpoints of excellent solvent resistance and ease of maintenance such as chemical cleaning. In addition, as the molecular weight cutoff value of the ultrafiltration membrane increases, the limiting flux increases, and the conductivity of the conductive composition obtained after purification tends to increase, but the yield tends to decrease. Similarly, the larger the pore size of the ultrafiltration membrane, the higher the limiting flux, and the higher the conductivity of the conductive composition obtained after purification tends to be, but the yield tends to be lower.
[0098] When refining an unpurified mixed liquid by membrane filtration, the filtration pressure depends on the ultrafiltration membrane and filtration device, but is preferably about 0.01 to 1.0 MPa in consideration of productivity. Furthermore, the filtration time is not particularly limited, but if other conditions are the same, the longer the filtration time, the higher the degree of purification and the conductive composition obtained after purification tends to have higher conductivity.
[0099] When the crude mixture is purified by anion exchange, for example, the crude mixture may be brought into contact with an anion exchange resin. The solid content of the unpurified mixed liquid is preferably 0.1 to 20% by mass, more preferably 0.1 to 10% by mass. If the solid content of the unpurified mixed liquid is 0.1% by mass or more, the purified mixed liquid can be easily recovered. On the other hand, if the solid content of the unpurified mixed liquid is 20% by mass or less, the viscosity does not increase too much, and the solid content can be efficiently contacted with the anion exchange resin, and the effect of ion exchange is fully exerted.
[0100] Anion exchange resins have numerous ion exchange groups (fixed ions) fixed to the resin matrix on the surface or inside the resin matrix. These ion exchange groups can selectively ion exchange (adsorb) and remove low molecular weight components generated by neutralizing the conductive polymer (A). In addition, the ion exchange groups can selectively ion exchange and capture anions that become impurities, and can also remove anions from unpurified mixed liquids.
[0101] Examples of the anion exchange resin include a strongly basic anion exchange resin and a weakly basic anion exchange resin. Among these, a strongly basic anion exchange resin is preferred because it has a high ion exchange capacity and can sufficiently remove low molecular weight components. Here, a "strong base" refers to a base with a large base dissociation constant, specifically, a degree of ionization close to 1 in an aqueous solution, which quantitatively produces hydroxide ions, and a base dissociation constant (pKb) of pKb<0 (Kb>1). On the other hand, a "weak base" refers to a base with a small base dissociation constant, specifically, a degree of ionization less than 1 and close to 0 in an aqueous solution, which has a weak ability to remove hydrogen ions from other substances.
[0102] Examples of the strongly basic anion exchange resin include anion exchange resins having quaternary ammonium salts, tertiary sulfonium bases, quaternary pyridinium bases, etc. as ion exchange groups. Commercially available products include "Orlite DS-2" manufactured by Organo Corporation and "Diaion SA10A" manufactured by Mitsubishi Chemical Corporation. On the other hand, examples of weakly basic anion exchange resins include anion exchange resins having primary to tertiary amino groups as ion exchange groups. Commercially available products include "Diaion WA20" manufactured by Mitsubishi Chemical Corporation and "Amberlite IRA67" manufactured by Organo Corporation.
[0103] When the unpurified mixed liquid is purified by contacting with an adsorbent, the contacting method is not particularly limited, and a method suitable for the application may be selected, such as a batch method or a column method.
[0104] The adsorbent is not particularly limited as long as it has a pore size sufficient and appropriate for the substance to be adsorbed to diffuse through the pores of the adsorbent and reach the adsorption surface, but synthetic adsorbents are preferred, and aromatic synthetic adsorbents are particularly preferred. Commercially available aromatic synthetic adsorbents include "Sepabeads SP850", "Sepabeads SP825L", and "Sepabeads SP700" manufactured by Mitsubishi Chemical Corporation.
[0105] The weight average molecular weight of the conductive polymer (A) in the mixed solution after purification is preferably 3,000 to 1,000,000, more preferably 5,000 to 800,000, even more preferably 10,000 to 500,000, and particularly preferably 11,000 to 100,000. If the weight average molecular weight is 3,000 or more, the conductivity, film-forming property, and film strength are excellent. In particular, if the weight average molecular weight is 10,000 or more, the generation of foreign matter during coating film formation can be further suppressed. On the other hand, if the weight average molecular weight is 1,000,000 or less, the solubility in a solvent is excellent. The weight average molecular weight of the conductive polymer in the mixed solution after purification is a value measured by carrying out the above-mentioned steps (i) to (iii).
[0106] In this manner, by heating the mixed liquid containing the conductive polymer (A) and the basic compound (B) and then purifying it, a conductive composition in which the area ratio (X / Y) is 0.046 or less can be obtained.
[0107] When the conductive composition contains a surfactant (C) or an optional component, the surfactant (C) or the optional component may be added to the mixed liquid in the heating step or the purification step, but it is preferable to add the surfactant (C) or the optional component to the mixed liquid after purification. If necessary, the mixed liquid after purification may be further diluted with a solvent (D). That is, the method for producing the conductive composition of this embodiment may include a step of adding a surfactant (C), a solvent (D), and, if necessary, an optional component to the mixed liquid after purification.
[0108] (Action and effect) The conductive composition of the first aspect of the present invention satisfies the above-mentioned condition 1, and therefore the defect-causing components are sufficiently reduced. Therefore, if the conductive composition of the first aspect of the present invention is used, foreign matter is unlikely to be generated when the conductive composition is made into a coating film. In addition, since the conductive composition of the first aspect of the present invention has a low ratio of defect-causing components, it is a new composition that differs from conventional compositions. Moreover, since the conductive composition of the first aspect of the present invention contains a basic compound (B) in addition to the conductive polymer (A), the conductive polymer (A) is neutralized. Therefore, by using the conductive composition of the first aspect of the present invention, a coating film in which acidic substances are unlikely to migrate to the resist layer can be formed, and the influence of film loss of the resist layer, etc. can be suppressed. Moreover, according to the above-mentioned method for producing a conductive composition, a conductive composition that satisfies the above condition 1 can be easily produced.
[0109] (Application) The conductive composition of the first aspect of the present invention is suitable for use in preventing static electricity in a resist layer. Specifically, the conductive composition of the first aspect of the present invention is applied to the surface of a resist layer in a pattern formation method using a charged particle beam and a chemically amplified resist to form a coating film. The coating film thus formed serves as an antistatic film for the resist layer. In addition to the above, the conductive composition according to the first aspect of the present invention can also be used as a material for, for example, capacitors, transparent electrodes, semiconductors, and the like.
[0110] When the coating film obtained from the conductive composition of the first aspect of the present invention is used as an antistatic film for a resist layer, the conductive composition of the first aspect of the present invention is applied to the surface of the resist layer by various coating methods, and then a pattern is formed by a charged particle beam. According to the present invention, the migration of acidic substances from the coating film (antistatic film) made of the conductive composition to the resist layer can be suppressed, and the original pattern shape of the resist layer can be obtained.
[0111] <Second aspect> The conductive composition according to the second aspect of the present invention contains a conductive polymer (A) and a basic compound (B). The conductive composition preferably further contains a surfactant (C) and a solvent (D). The conductive polymer (A), the basic compound (B), the surfactant (C) and the solvent (D) may each be those exemplified above in the explanation of the first embodiment.
[0112] The conductive composition according to the second aspect of the present invention satisfies the following condition 2. Condition 2: ZS / ZR is 20 or less. Here, the ZS is the maximum value of the fluorescence intensity in the wavelength range of 320 to 420 nm when the fluorescence spectrum of a measurement solution obtained by diluting the conductive composition with water so that the solid content concentration of the conductive polymer (A) is 0.6 mass % is measured using a spectrofluorophotometer at an excitation wavelength of 230 nm. The ZR is the maximum value of Raman scattering intensity in the wavelength range of 380 to 420 nm when the fluorescence spectrum of water is measured at an excitation wavelength of 350 nm using a spectrofluorometer.
[0113] The maximum value of the fluorescence intensity (ZS) in the wavelength region of 320 to 420 nm is specifically measured as follows using a spectrofluorometer. The conductive composition is diluted with water to a solids concentration of the conductive polymer (A) of 0.6% by mass, and the measurement solution is placed in a cell for measuring surface fluorescence (triangular cell), and a fluorescence spectrum is obtained using a spectrofluorophotometer under the following measurement condition 1. The obtained fluorescence spectrum is corrected with an instrument function determined separately using Rhodamine B for a spectrofluorophotometer. For the corrected fluorescence spectrum, the maximum value of the fluorescence intensity (ZS) of the measurement solution is determined from the maximum peak height in the wavelength region of 320 to 420 nm. (Measurement condition 1) Excitation wavelength: 230nm Fluorescence measurement wavelength: 250~450nm Bandwidth: 10nm on the excitation side, 5nm on the emission side Response time: 2 seconds Scanning speed: 100nm / min
[0114] The maximum value (ZR) of the Raman scattering intensity in the wavelength region of 380 to 420 nm is specifically measured as follows using a spectrofluorometer. Water is placed in a surface fluorescence measurement cell (triangular cell) and a fluorescence spectrum is obtained using a spectrofluorophotometer under measurement condition 2 below. The obtained fluorescence spectrum is corrected with an instrument function determined separately using rhodamine B for a spectrofluorophotometer. For the corrected fluorescence spectrum, the maximum value of the Raman scattering intensity of water (ZR) is determined from the maximum peak height in the wavelength region of 380 to 420 nm. (Measurement condition 2) Excitation wavelength: 350nm Fluorescence measurement wavelength: 350~450nm Bandwidth: 10nm on the excitation side, 5nm on the emission side Response time: 2 seconds Scanning speed: 100nm / min
[0115] When the fluorescence spectrum is measured at an excitation wavelength of 230 nm, the peaks appearing in the wavelength range of 320 to 420 nm are mainly due to defect-causing components (low molecular weight components). If the ZS / ZR is 20 or less, the proportion of defect-causing components (low molecular weight components) contained in the conductive composition is low, so that foreign matter is less likely to occur in the coating film formed from the conductive composition. In addition, a ZS / ZR of 20 or less means that the proportion of fluorescent material in the conductive composition is also low. The smaller the ZS / ZR, the smaller the proportion of low molecular weight components contained in the conductive composition. Therefore, the smaller the ZS / ZR, the more preferable it is. Specifically, ZS / ZR is preferably 10 or less, and more preferably 5 or less. Also, ZS / ZR is preferably 0 or more. That is, ZS / ZR is 0 to 20, preferably 0 to 10, and more preferably 0 to 5.
[0116] In order to obtain a conductive composition having a ZS / ZR of 20 or less, for example, a purification step may be introduced into the production of the conductive composition. An example of a method for producing the conductive composition will now be described.
[0117] (Manufacturing method) The method for producing the conductive composition of this embodiment includes a step of heat-treating a mixed liquid containing a conductive polymer (A) and a basic compound (B) (heating step), and a step of purifying the mixed liquid after heating (purification step) so that ZS / ZR is 20 or less.
[0118] The specific methods in the heating step and the purification step in this embodiment are the same as those in the heating step and the purification step in the method for producing a conductive composition of the first aspect. A mixed liquid containing the conductive polymer (A) and the basic compound (B) is heated and then purified to obtain a conductive composition having a ZS / ZR of 20 or less.
[0119] When the conductive composition contains a surfactant (C) or an optional component, the surfactant (C) or the optional component may be added to the mixed liquid in the heating step or the purification step, but it is preferable to add the surfactant (C) or the optional component to the mixed liquid after purification. If necessary, the mixed liquid after purification may be further diluted with a solvent (D). That is, the method for producing the conductive composition of this embodiment may include a step of adding a surfactant (C), a solvent (D), and, if necessary, an optional component to the mixed liquid after purification.
[0120] (Action and effect) The conductive composition of the second aspect of the present invention satisfies the above condition 2, and therefore the defect-causing components are sufficiently reduced. Therefore, if the conductive composition of the second aspect of the present invention is used, foreign matter is unlikely to be generated when the conductive composition is made into a coating film. Furthermore, the conductive composition of the second aspect of the present invention is a new composition that differs from conventional compositions, since it contains a small proportion of fluorescent material in addition to the defect-causing components. Moreover, the conductive composition of the second aspect of the present invention contains a basic compound (B) in addition to the conductive polymer (A), and thus the conductive polymer (A) is neutralized. Therefore, by using the conductive composition of the second aspect of the present invention, a coating film in which acidic substances are unlikely to migrate to the resist layer can be formed, and the effects of film loss of the resist layer, etc. can be suppressed. Moreover, according to the above-mentioned method for producing a conductive composition, a conductive composition that satisfies the above condition 2 can be easily produced.
[0121] (Application) The use of the conductive composition according to the second embodiment of the present invention is the same as the use of the conductive composition according to the first embodiment.
[0122] [conductor] The conductor of the third aspect of the present invention has a substrate and a coating formed by applying the conductive composition of the first or second aspect of the present invention onto at least one surface of the substrate. An example of the method for producing a conductor of the present invention will now be described.
[0123] The method for producing an electric conductor of this embodiment includes a step of applying the conductive composition of the first or second aspect of the present invention to at least one surface of a substrate to form a coating film (a coating step). The substrate may be, for example, plastic, wood, paper, ceramics, films thereof, or glass plates, etc. Among these, plastics and films thereof are particularly preferred from the viewpoint of adhesion. Examples of plastics and polymeric compounds used in plastic films include polyethylene, polyvinyl chloride, polypropylene, polystyrene, ABS resin, AS resin, methacrylic resin, polybutadiene, polycarbonate, polyarylate, polyvinylidene fluoride, polyester, polyamide, polyimide, polyaramid, polyphenylene sulfide, polyether ether ketone, polyphenylene ether, polyether nitrile, polyamide imide, polyether sulfone, polysulfone, polyether imide, polyethylene terephthalate, polybutylene terephthalate, polyurethane, and the like. In order to improve adhesion to the conductive polymer film, the surface of the plastic substrate or film thereof on which the conductive polymer film is to be formed may be previously subjected to a corona surface treatment or plasma treatment.
[0124] The method for applying the conductive composition onto the substrate can be a method generally used for coating, such as a coating method using a gravure coater, a roll coater, a curtain flow coater, a spin coater, a bar coater, a reverse coater, a kiss coater, a fountain coater, a rod coater, an air doctor coater, a knife coater, a blade coater, a cast coater, or a screen coater, a spraying method such as spray coating, or an immersion method such as dipping. The conductive composition is preferably applied onto a substrate so that the coating film has a thickness of 5 to 150 nm after drying.
[0125] After the conductive composition is applied onto the substrate to form a coating film, the coating film may be left as it is at room temperature (25° C.) or may be subjected to a heat treatment. When heat treatment is performed, the heat treatment temperature is preferably from 40 to 250°C, more preferably from 50 to 200°C. The heat treatment time is preferably 0.5 minutes to 1 hour, more preferably 1 to 50 minutes.
[0126] <Action and effect> The conductor of the third aspect of the present invention described above has a coating film formed from the conductive composition of the first or second aspect of the present invention, and therefore has high conductivity and also suppresses the generation of foreign matter. Furthermore, according to the above-mentioned method for producing a conductor, since the conductive composition of the first or second aspect of the present invention is used, a conductor having high conductivity and suppressing the generation of foreign matter can be produced even if the coating film is left at room temperature or is heat-treated.
[0127] Other aspects of the present invention are as follows. <1> A conductive composition comprising a conductive polymer (A) having an acidic group and a basic compound (B), A conductive composition in which the area ratio (X / Y) calculated by an evaluation method including the steps (I) to (VI) is 0.046 or less, preferably 0.001 to 0.046, and more preferably 0.001 to 0.040. <2> A conductive composition comprising a conductive polymer (A) having an acidic group and a basic compound (B), The conductive composition has ZS / ZR of 20 or less, preferably 0 to 10, and more preferably 0 to 5. <3> The conductive polymer (A) has a monomer unit represented by the general formula (5). <1> or <2> A conductive composition. <4> The content of the conductive polymer (A) is 0.1 to 5 mass %, more preferably 0.2 to 3 mass %, and further preferably 0.5 to 2 mass %, based on the total mass of the conductive composition. <1> ~ <3> Any of the conductive compositions. <5> The content of the conductive polymer (A) is 50 to 99.9 mass%, more preferably 80 to 99.9 mass%, and further preferably 95 to 99.9 mass%, based on the total mass of the solid content of the conductive composition. <1> ~ <4> Any of the conductive compositions. <6> the basic compound (B) is at least one selected from the group consisting of the quaternary ammonium compound (b-1), the basic compound (b-2) and the basic compound (b-3), and is preferably at least one selected from the group consisting of the quaternary ammonium compound (b-1) and the basic compound (b-2); <1> ~ <5> Any of the conductive compositions. <7> The basic compound (B) is the basic compound (b-2), and is preferably tetrabutylammonium hydroxide. <6> A conductive composition. <8> the content of the basic compound (B) is 0.1 to 1 mol equivalent relative to 1 mol of units having an acidic group among units constituting the conductive polymer (A), more preferably 0.1 to 0.9 mol equivalent, and further preferably 0.25 to 0.85 mol equivalent; <1> ~ <7> Any of the conductive compositions. <9> Further comprising a surfactant (C) and a solvent (D); <1> ~ <8> Any of the conductive compositions. <10> The surfactant (C) is a water-soluble polymer having the nitrogen-containing functional group and a terminal hydrophobic group. <9> A conductive composition. <11> the content of the surfactant (C) is 5 to 80 parts by mass, more preferably 10 to 70 parts by mass, and further preferably 10 to 60 parts by mass, relative to 100 parts by mass of the total of the conductive polymer (A), the basic compound (B), and the surfactant (C); <9> or <10> A conductive composition. <12> The solvent (D) is water or an alcohol. <9> ~ <11> Any of the conductive compositions. <13> The content of the solvent (D) is 1 to 99 mass%, more preferably 10 to 98 mass%, and further preferably 50 to 98 mass%, based on the total mass of the conductive composition. <9> ~ <12> Any of the conductive compositions. <14> A substrate and, on at least one surface of the substrate, <1> ~ <13> and a coating film formed by applying any one of the conductive compositions described above. <15> On at least one surface of the substrate, <1> ~ <13> A method for producing an electric conductor, comprising applying any one of the conductive compositions described above to form a coating film.
[0128] <16> A step of heat-treating a mixed liquid containing the conductive polymer (A) having an acidic group and the basic compound (B) (heating step); a step of purifying the mixture after heating so that the area ratio (X / Y) calculated by the evaluation method including the steps (i) to (vi) is 0.046 or less, preferably 0.001 to 0.046, and more preferably 0.001 to 0.040 (purification step); The method for producing a conductive composition comprising the steps of: <17> A step of heat-treating a mixed liquid containing the conductive polymer (A) having an acidic group and the basic compound (B) (heating step); a step of purifying the mixture after heating so that the ZS / ZR is 20 or less, preferably 0 to 10, and more preferably 0 to 5 (a purification step); The method for producing a conductive composition comprising the steps of: <18> The heating temperature in the heating step is 40°C or higher, more preferably 60 to 80°C. <16> or <17> A method for producing the conductive composition. <19> The purification method of the mixture in the purification step is at least one selected from the group consisting of a membrane filtration method, an anion exchange method, and a contact method with an adsorbent. <16> ~ <18> 2. A method for producing a conductive composition according to claim 1 . <20> The filtration membrane used in the membrane filtration method is a microfiltration membrane or an ultrafiltration membrane, more preferably a nylon filter; <19> A method for producing the conductive composition. <21> The anion exchange resin used in the anion exchange method is a strong basic anion exchange resin or a weak basic anion exchange resin, more preferably a strong basic anion exchange resin. <19> or <20> A method for producing the conductive composition. <22> The adsorbent used in the contact method with the adsorbent is a synthetic adsorbent, more preferably an aromatic synthetic adsorbent. <19> ~ <21> 2. A method for producing a conductive composition according to claim 1 . <23> The conductive polymer (A) has a monomer unit represented by the general formula (5). <16> ~ <22> 2. A method for producing a conductive composition according to claim 1 . <24> the basic compound (B) is at least one selected from the group consisting of the quaternary ammonium compound (b-1), the basic compound (b-2) and the basic compound (b-3), and is preferably at least one selected from the group consisting of the quaternary ammonium compound (b-1) and the basic compound (b-2); <16> ~ <23> 2. A method for producing a conductive composition according to claim 1 . <25> The basic compound (B) is the basic compound (b-2), and is preferably tetrabutylammonium hydroxide. <24> A method for producing the conductive composition. <26> adding a surfactant (C) and a solvent (D) to the purified mixture; <16> ~ <25> 2. A method for producing a conductive composition according to claim 1 . <27> The surfactant (C) is a water-soluble polymer having the nitrogen-containing functional group and a terminal hydrophobic group. <26> A method for producing the conductive composition. <28> The solvent (D) is water or an alcohol. <26> or <27> A method for producing the conductive composition. EXAMPLES
[0129] The present invention will now be described in more detail with reference to examples, but the following examples are not intended to limit the scope of the present invention. The various measurement and evaluation methods used in the examples and comparative examples are as follows.
[0130] [Measurement and evaluation method] <Calculation of area ratio (X / Y)> First, an eluent was prepared by adding sodium carbonate and sodium bicarbonate to a mixed solvent of water (ultrapure water) and methanol in a volume ratio of water:methanol = 8:2, so that the solid concentrations were 20 mmol / L and 30 mmol / L, respectively. The pH of the obtained eluent at 25°C was 10.8. The purified mixed liquid containing the conductive polymer (A) and the basic compound (B) was dissolved in this eluent so that the solid content concentration of the conductive polymer (A) was 0.1 mass %, thereby preparing a test solution (step (i)). The molecular weight distribution of the obtained test solution was measured using a polymer material evaluation device equipped with a gel permeation chromatograph connected to a photodiode array (PDA) detector (Waters Corporation, "Waters Alliance 2695, 2414 (refractometer), 2996 (PDA)"), and a chromatogram was obtained (step (ii)). Next, for the obtained chromatogram, the retention time was converted to the molecular weight (M) in terms of sodium polystyrene sulfonate (step (iii)). Specifically, sodium polystyrene sulfonate with peak top molecular weights of 206, 4300, 6800, 17000, 32000, 77000, 15000, and 2600000 was used as the standard sample. In the same manner as the test solution, each standard sample was dissolved in the eluent so that the solid content concentration was 0.05% by mass, except that the standard sample with a peak top molecular weight of 206 was dissolved in the eluent so that the solid content concentration was 0.0025% by mass, to prepare standard solutions. Then, for each standard solution, the relationship between the retention time and the molecular weight was determined by GPC, and a calibration curve was created. From the created calibration curve, for the chromatogram obtained in step (ii), the retention time was converted to the molecular weight (M) in terms of sodium polystyrene sulfonate. Then, the area (X) in the region where the molecular weight (M) is 300 to 3300 and the area (Y) of the entire region derived from the conductive polymer (A) were determined (steps (iv) and (v)). The area ratio (X / Y) of these areas (X) and area (Y) was determined (step (vi)).
[0131] <Calculation of (ZS / ZR)> First, a measurement solution obtained by diluting the conductive composition with water so that the solid content concentration of the conductive polymer (A) was 0.6% by mass was placed in a surface fluorescence measurement cell (triangle cell), and a fluorescence spectrum was acquired using a spectrofluorometer under the following measurement condition 1. The acquired fluorescence spectrum was corrected with an instrument function separately obtained using rhodamine B for the spectrofluorometer. For the corrected fluorescence spectrum, the maximum value (ZS) of the fluorescence intensity of the measurement solution was determined from the maximum peak height in the wavelength region of 320 to 420 nm. (Measurement condition 1) · Measuring device: Spectrofluorometer (manufactured by JASCO Corporation, "FP - 6500") · Excitation wavelength: 230 nm · Fluorescence measurement wavelength: 250 to 450 nm · Bandwidth: 10 nm on the excitation side and 5 nm on the fluorescence side · Response: 2 sec · Scanning speed: 100 nm / min
[0132] Next, water was placed in a surface fluorescence measurement cell (triangular cell), and a fluorescence spectrum was obtained using a spectrofluorometer under the following measurement condition 2. The obtained fluorescence spectrum was corrected with an instrument function determined separately using Rhodamine B for a spectrofluorometer. For the corrected fluorescence spectrum, the maximum value of the Raman scattering intensity of water (ZR) was determined from the maximum peak height in the wavelength region of 380 to 420 nm. ZS / ZR was calculated by dividing ZS by ZR. (Measurement condition 2) Excitation wavelength: 350nm Fluorescence measurement wavelength: 350~450nm Bandwidth: 10nm on the excitation side, 5nm on the emission side Response time: 2 seconds Scanning speed: 100nm / min
[0133] <Evaluation of foreign matter occurrence> The conductive composition was spin-coated (1000 rpm x 180 sec) onto an 8-inch silicon wafer as a substrate, and heated on a hot plate at 80°C for 2 minutes to obtain a test specimen having a coating film (film thickness 20 nm) formed on the substrate. The obtained test piece was observed under a microscope (magnification: 1000 times) using a SEM linked to an optical wafer appearance inspection device (manufactured by Hitachi High-Technologies Corporation, "SR-7300"), and the coating film was measured at 1 mm 2 The number of foreign bodies (α) that occurred per unit area was counted. Similarly, for an 8-inch silicon wafer before applying the conductive composition, 2 The number of foreign matters (β) present per unit area was measured, and the number of foreign matters originating from the conductive composition (α-β) was calculated. The occurrence of foreign matters was evaluated according to the following evaluation criteria. A: The number of foreign matter originating from the conductive composition is 10 or less. B: The number of foreign matter originating from the conductive composition is 11 to 20. C: The number of foreign matter originating from the conductive composition is 21 or more.
[0134] <Measurement of surface resistance> Test pieces were prepared in the same manner as in the evaluation of the occurrence of foreign matter. The surface resistance value of the obtained test piece was measured using a resistivity meter ("Loresta GP" manufactured by Mitsubishi Chemical Analytech Co., Ltd.) equipped with an in-line four-point probe.
[0135] [Production of conductive polymer (A)] <Production Example 1: Production of Conductive Polymer (A-1)> 10 mol of 3-aminoanisole-4-sulfonic acid was dissolved in 5820 mL of a 4 mol / L pyridine solution (solvent: water / acetonitrile=3 / 7 (mass ratio)) at 40° C. to obtain a monomer solution. Separately, 10 mol of ammonium peroxodisulfate was dissolved in 8,560 mL of a solution of water / acetonitrile=3 / 7 (mass ratio) to obtain an oxidizing agent solution. Next, the monomer solution was added dropwise while cooling the oxidant solution to 5°C. After the completion of the dropwise addition, the mixture was further stirred at 25°C for 15 hours, then heated to 35°C and further stirred for 2 hours to obtain a conductive polymer. The reaction mixture containing the obtained conductive polymer was then filtered using a centrifugal filter. The mixture was further washed with methanol and dried to obtain 433 g of a powdered conductive polymer (A-1).
[0136] <Production Example 2: Production of Conductive Polymer Solution (A1-1)> 20 g of the conductive polymer (A-1) obtained in Production Example 1 was dissolved in 980 g of pure water to obtain 1000 g of a conductive polymer solution (A-1-1) having a solid content concentration of 2 mass %. The column was packed with 500 mL of a cation exchange resin ("Amberlite IR-120B", manufactured by Organo Corporation) that had been washed with ultrapure water. 1000 g of the conductive polymer solution (A-1-1) was passed through this column at a rate of 50 mL / min (SV=6) to obtain 900 g of a conductive polymer solution (A1-1-1) from which basic substances and the like had been removed. Next, 500 mL of anion exchange resin ("Amberlite IRA410", manufactured by Organo Corporation) that had been washed with ultrapure water was packed into the column. 900 g of the conductive polymer solution (A1-1-1) was passed through this column at a rate of 50 mL / min (SV=6) to obtain 800 g of the conductive polymer solution (A1-1) from which basic substances and the like had been removed. The composition of the conductive polymer solution (A1-1) was analyzed by ion chromatography, and it was found that 80% by mass of the residual monomer, 99% by mass of the sulfate ion, and 99% by mass or more of the basic substance (pyridine) were removed. The heating residue was measured and found to be 2.0% by mass. In other words, the solid content of the conductive polymer solution (A1-1) was 2.0% by mass. In addition, 1 Sverdrup (SV) is 1 x 106 m 3 / s (1GL / s).
[0137] [Production of surfactant (C)] <Production Example 3: Production of Water-Soluble Polymer (C-1) Having Nitrogen-Containing Functional Group and Terminal Hydrophobic Group> 55g of N-vinyl-2-pyrrolidone, 3g of azobisisobutyronitrile as a polymerization initiator, and 1g of n-dodecyl mercaptan as a chain transfer agent were added dropwise to isopropyl alcohol that had been heated to an internal temperature of 80°C in advance, while maintaining the internal temperature at 80°C, to perform dropwise polymerization. After completion of the dropwise addition, the mixture was aged for another 2 hours at an internal temperature of 80°C, then allowed to cool, concentrated under reduced pressure, and redissolved in a small amount of acetone. The acetone solution of the obtained polymer was dropped into excess n-hexane to obtain a white precipitate, which was then filtered, washed, and dried to obtain 45g of a water-soluble polymer (C-1).
[0138] [Example 1] Conductive polymer solution (A1-1) 100 parts by mass (2 parts by mass in terms of solid content (3.1 × 10 -3 The mixture (corresponding to 100 parts by mass of the basic compound (B)) was heated to 70°C and 90 parts by mass of tetrabutylammonium hydroxide (TBAH) was added as the basic compound (B) while stirring to obtain a mixed liquid (conductive polymer-containing liquid). The resulting mixed liquid was heated to maintain the temperature at 70°C, and stirring was performed for 2 hours from the start of the addition of the basic compound (B) (heating step). The amount of the basic compound (B) added corresponds to 0.40 mol equivalents per 1 mol of units having an acidic group among the units constituting the conductive polymer (A).
[0139] Next, the heated mixture was left at room temperature for 60 minutes, and then 50 g of the mixture was passed through a filter at a constant pressure of 0.05 MPa using a pressure filtration device (purification step). A nylon filter (Ny-10 nm) with a pore size of 10 nm was used as the filter. A part of the obtained filtrate (mixture after purification) was collected and dissolved in the previously prepared eluent so that the solid content concentration of the conductive polymer (A) was 0.1 mass % to prepare a test solution. The area ratio (X / Y) of this test solution was calculated. The results are shown in Table 1. Separately, a portion of the resulting filtrate (mixture after purification) was sampled, and the fluorescence intensity was measured to determine ZS / ZR. The results are shown in Table 1.
[0140] Next, 1 part by mass of the water-soluble polymer (C-1) and 89 parts by mass of isopropyl alcohol as the solvent (D) were added to 10 parts by mass of the purified mixed liquid to obtain a conductive composition. The conductive composition thus obtained was used to evaluate the generation of foreign matter. The results are shown in Table 1. The surface resistance value was also measured. The results are shown in Table 1.
[0141] [Example 2] The heating step was carried out in the same manner as in Example 1. Next, the heated mixture was left at room temperature for 60 minutes, and then 10 parts by mass of a strongly basic anion exchange resin (Organo Corporation, "Orlite DS-2") was added to the unpurified mixture, and the mixture was rotated at a rotation speed of 50 rpm at room temperature for 1 hour using a Mix Rotor Variable (VMR-3R). The strongly basic anion exchange resin was then removed by filtering the mixture through a filter with a pore size of 0.45 μm (purification step). A portion of the resulting filtrate (mixture after purification) was collected, and the area ratio (X / Y) was calculated in the same manner as in Example 1. The results are shown in Table 1. Separately, a portion of the resulting filtrate (mixture after purification) was collected, and the fluorescence intensity was measured to determine ZS / ZR. The results are shown in Table 1 and Figure 2. A conductive composition was prepared in the same manner as in Example 1, except that the resulting purified mixed liquid was used, and the generation of foreign matter was evaluated. The results are shown in Table 1. The surface resistance value was also measured. The results are shown in Table 1.
[0142] [Example 3] The heating step was carried out in the same manner as in Example 1. Separately, 10 g of a synthetic adsorbent (Mitsubishi Chemical Corporation, "Sepabeads SP850") was weighed out into a PP cup and rinsed eight times with 50 g of ultrapure water (Millipore). Next, the heated mixture was left at room temperature for 60 minutes, and then 20 g of the unpurified mixture was added to the washed synthetic adsorbent so that the solid content concentration of the washed synthetic adsorbent was 2.0 mass%, and the mixture was rotated at a rotation speed of 150 rpm at room temperature for 1 hour using a slim stirrer. Then, the synthetic adsorbent was removed by filtering the mixture through a filter with a pore size of 0.45 μm (purification process). A portion of the resulting filtrate (mixture after purification) was collected, and the area ratio (X / Y) was calculated in the same manner as in Example 1. The results are shown in Table 1. Separately, a portion of the resulting filtrate (mixture after purification) was sampled, and the fluorescence intensity was measured to determine ZS / ZR. The results are shown in Table 1. A conductive composition was prepared in the same manner as in Example 1, except that the resulting purified mixed liquid was used, and the generation of foreign matter was evaluated. The results are shown in Table 1. The surface resistance value was also measured. The results are shown in Table 1.
[0143] [Comparative Example 1] The heating step was carried out in the same manner as in Example 1. After the mixture was heated and left to stand at room temperature for 60 minutes, a portion of the unrefined mixture was sampled, and the area ratio (X / Y) was calculated in the same manner as in Example 1. The results are shown in Table 1. Separately, a portion of the resulting filtrate (mixture after purification) was collected, and the fluorescence intensity was measured to determine ZS / ZR. The results are shown in Table 1 and Figure 2. A conductive composition was prepared in the same manner as in Example 1, except that the unrefined mixed liquid was used, and the generation of foreign matter was evaluated. The results are shown in Table 1. The surface resistance was also measured. The results are shown in Table 1.
[0144] [Table 1]
[0145] As is clear from Table 1 and Figure 2, the conductive composition obtained in each Example had a sufficiently reduced amount of defect-causing components, and the coating film formed from the conductive composition obtained in each Example had suppressed generation of foreign matter. On the other hand, the conductive composition obtained in Comparative Example 1 contained more defect-causing components than the other Examples, and the number of foreign matters generated in the coating film was also greater than the other Examples. [Industrial Applicability]
[0146] The conductive composition of the present invention has sufficiently reduced defect-causing components, and is capable of forming a conductive film with excellent conductivity and with little loss of the resist layer, and is therefore useful for preventing static electricity in resists.
Claims
1. A conductive composition comprising a conductive polymer (A) having an acidic group and a basic compound (B), The conductive polymer (A) contains a monomer unit represented by the following general formula (5) in an amount of 10 to 100 mol % based on all units (100 mol %) constituting the conductive polymer (A), An electroconductive composition (excluding those containing a polymer obtained by polymerizing a thiophene derivative), in which the area ratio (X / Y) of the electroconductive composition is 0.046 or less, as calculated by an evaluation method including the following steps (I) to (VI): (I) A step of preparing a test solution by adding sodium carbonate and sodium bicarbonate to an eluent prepared by mixing water and methanol in a volume ratio of water:methanol = 8:2, so that the solid concentration of the conductive polymer (A) is 0.1 mass %, and dissolving the conductive composition in the eluent. (II) A step of measuring the molecular weight distribution of the test solution using a Waters Alliance 2695, 2414 (refractometer), 2996 (PDA) equipped with a gel permeation chromatograph connected to a photodiode array (PDA) detector, manufactured by Waters Corporation, to obtain a chromatogram. (III) A step of converting the retention times of the chromatogram obtained in the step (II) into molecular weights (M) in terms of sodium polystyrene sulfonate using sodium polystyrene sulfonate having peak top molecular weights of 206, 4,300, 6,800, 17,000, 32,000, 77,000, 15,000, and 2,600,000 as standard samples. (IV) A step of determining the area (X) of a region having a molecular weight (M) of 300 to 3,300 in terms of the molecular weight (M) of sodium polystyrene sulfonate. (V) A step of determining the area (Y) of the entire region derived from the conductive polymer (A) in terms of the molecular weight (M) of sodium polystyrene sulfonate. (VI) A step of calculating the area ratio (X / Y) between the area (X) and the area (Y). 【Chemistry 1】 In formula (5), R 18 ~R 21 each independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 24 carbon atoms, a linear or branched alkoxy group having 1 to 24 carbon atoms, an acidic group, a hydroxyl group, a nitro group, or a halogen atom (-F, -Cl, -Br, or I). 18 ~R 21 At least one of the groups is an acidic group or a salt thereof.
2. The conductive composition according to claim 1 , further comprising a surfactant (C) and a solvent (D).
3. In the general formula (5), R 18 ~R 21 The conductive composition according to claim 1 or 2, wherein one of the above is a linear or branched alkoxy group having 1 to 4 carbon atoms, the other is a sulfonic acid group, and the remaining is hydrogen.
4. A conductor comprising a substrate and a coating film formed by applying the conductive composition according to any one of claims 1 to 3 onto at least one surface of the substrate.
5. A method for producing an electric conductor, comprising applying the conductive composition according to any one of claims 1 to 3 onto at least one surface of a substrate to form a coating film.
6. a step of heating a mixed liquid containing the conductive polymer (A) having an acidic group and the basic compound (B) to 40° C. or higher; A step of purifying the mixed liquid after heating so that the area ratio (X / Y) calculated by an evaluation method including the following steps (i) to (vi) is 0.046 or less; having The conductive polymer (A) contains a monomer unit represented by the following general formula (5) in an amount of 10 to 100 mol % based on all units (100 mol %) constituting the conductive polymer (A). (i) A step of preparing a test solution by dissolving the purified mixed solution in an eluent prepared by adding sodium carbonate and sodium bicarbonate to a mixed solvent obtained by mixing water and methanol so that the volume ratio of water:methanol is 8:2, so that the solid concentration of the conductive polymer (A) is 0.1 mass %. (ii) A step of measuring the molecular weight distribution of the test solution using a Waters Alliance 2695, 2414 (refractometer), 2996 (PDA) equipped with a gel permeation chromatograph connected to a photodiode array (PDA) detector, manufactured by Waters, to obtain a chromatogram. (iii) A step of converting the retention times of the chromatogram obtained in the step (ii) into molecular weights (M) in terms of sodium polystyrene sulfonate using sodium polystyrene sulfonate having peak top molecular weights of 206, 4,300, 6,800, 17,000, 32,000, 77,000, 15,000, and 2,600,000 as standard samples. (iv) A step of determining the area (X) of a region having a molecular weight (M) of 300 to 3,300 in terms of the molecular weight (M) calculated as sodium polystyrene sulfonate. (v) A step of determining the area (Y) of the entire region derived from the conductive polymer (A) in terms of the molecular weight (M) of sodium polystyrene sulfonate. (vi) determining the area ratio (X / Y) of the area (X) to the area (Y). 【Chemistry 2】 In formula (5), R 18 ~R 21 each independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 24 carbon atoms, a linear or branched alkoxy group having 1 to 24 carbon atoms, an acidic group, a hydroxyl group, a nitro group, or a halogen atom (-F, -Cl, -Br, or I). 18 ~R 21 At least one of the groups is an acidic group or a salt thereof.
7. The method for producing a conductive composition according to claim 6 , further comprising the step of adding a surfactant (C) and a solvent (D) to the purified mixed liquid.
8. In the general formula (5), R 18 ~R 21 Among the above, any one of them is a linear or branched alkoxy group having 1 to 4 carbon atoms, any one of them is a sulfonic acid group, and the remaining are hydrogen. The method for producing a conductive composition according to claim 6 or 7.
Citation Information
Patent Citations
Conductive composite material and solid electrolytic capacitor prepared therewith
JP2016124889A
Conductor, conductive composition, and laminate
WO2014017540A1